1980
DOI: 10.1139/v80-080
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of aurodox and related antibiotics

Abstract: The studies which led to the complete structure elucidation of the antibiotic aurodox, including the chiralities of all eleven asymmetric centers and the cis–trans isomerism of all seven exocyclic double bonds, are summarized. Aurodox was correlated stereochemically with mocimycin. Thus, aurodox can be described as N-[7-[5(R)-[7-[1,2-dihydro-4-hydroxy-1-methyl-2-oxo-3-pyridinyl]-6-methyl-7-oxo-1(E),3(E),5(E)-heptatrienyl]tetrahydro-3(S),4(R)-dihydroxyfuran-2(S)-yl]-6(S)-methoxy-5,7(R)-dimethyl-2(E),4(E)-heptad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Preparation of the Ternary Complex EF-Tu⅐GDP⅐Aurodox-Since aurodox was reported to be moderately sensitive to light (21), exposure was kept at a minimum. Because of its extremely low solubility in water, a 120 mM alcoholic solution was prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of the Ternary Complex EF-Tu⅐GDP⅐Aurodox-Since aurodox was reported to be moderately sensitive to light (21), exposure was kept at a minimum. Because of its extremely low solubility in water, a 120 mM alcoholic solution was prepared.…”
Section: Methodsmentioning
confidence: 99%
“…[388][389][390][391][392][393][394][395][396][397][398][399][400][401] For 228 and some other congeners it was shown that the activity relies on an inhibition of elongation factor Tu (EF-Tu), [402][403][404][405][406] which plays a key role in protein biosynthesis by mediating the entry of aminoacyl-tRNAs into the ribosome. [407][408][409] For this reason, the name elfamycins was proposed for this compound family.…”
Section: Kirromycinmentioning
confidence: 99%
“…Interestingly, a total of nine compounds, including a novel compound 1, were purified from the culture of NBRC 105896. These include indolactam V, 20 mocimycin, 21 5,6-dihydromocimycin, 22 N-demethylteleocidin A 1 , 23 1 and teleocidin A 1 24 from the mycelial extract, and factumycin 25 and kirrothricin 22 from the supernatant extract of the culture. Levorin A 2 26 was also detected in the culture grown in a production medium containing 1% HP-20 (Mitsubishi Chemical, Tokyo, Japan).…”
mentioning
confidence: 99%